2015
DOI: 10.1093/eurheartj/ehv550
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative thresholds for mid-to-late haemodynamic and clinical outcomes after pulmonary valve replacement in tetralogy of Fallot

Abstract: In TOF patients who had undergone PVR, the best preoperative threshold to achieve mid-to-late RV normalization was RV ESV < 80 mL/m(2). Patients with preoperative RV ESV > 95 mL/m(2) were at increased risk for suboptimal haemodynamic outcome and adverse clinical events. Our findings may assist in timing of PVR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
60
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(68 citation statements)
references
References 32 publications
3
60
1
4
Order By: Relevance
“…The incidence of death in our population is somewhat higher than previously reported19 but is driven by three cases where death occurred as a result of extracardiac complications following PVR and may be a reflection of our higher risk, quaternary care practice. Worthy of mention is the trend towards increased number of heart failure events in patients with more severe fibrosis pre-PVR which is in keeping with the presence of decreased LV systolic function in the severe fibrosis group (median LVEF 51%) as compared with the remainder of the population (median LVEF 56%).…”
Section: Discussioncontrasting
confidence: 60%
“…The incidence of death in our population is somewhat higher than previously reported19 but is driven by three cases where death occurred as a result of extracardiac complications following PVR and may be a reflection of our higher risk, quaternary care practice. Worthy of mention is the trend towards increased number of heart failure events in patients with more severe fibrosis pre-PVR which is in keeping with the presence of decreased LV systolic function in the severe fibrosis group (median LVEF 51%) as compared with the remainder of the population (median LVEF 56%).…”
Section: Discussioncontrasting
confidence: 60%
“…The medical management of adults with TOF requires assessment and, if necessary, treatment of haemodynamic residual lesions such as pulmonary regurgitation 2. In addition, there remain concerns about sudden cardiac death, for which appropriate risk stratification strategies are needed 19 20.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with tetralogy of Fallot (TOF), right ventricular (RV) dysfunction is thought to contribute to late complications and has been related with QRS duration 1 2 7. Severe QRS prolongation has been widely recognised as a risk factor for mortality in adults with TOF 1–3 7–10.…”
Section: Introductionmentioning
confidence: 99%
“…A cardiac magnetic resonance-based study suggested that a preoperative Right Ventricular End-Systolic Volume index (RVESVi) cut-off of ≤82 mL/m 2 was equally sensitive and more specific for normalisation of RV volumes compared with our preoperative Right Ventricular End-Diastolic Volume index (RVEDVi) threshold of ≤158 mL/m 2 , justifying the use of RVESVi for clinical timing for PVR 2. In 2016, Bokma et al concluded that preoperative RVESVi <80 mL/m 2 was the best threshold to achieve mid-to-late RV normalisation 3. The impact of abnormal RV mechanics on the left ventricle (LV) has been appreciated, with the assessment of LV assuming higher priority in decision-making.…”
mentioning
confidence: 67%